VizieR Online Data Catalog: High-precision radial velocities for HD 221416 (Huber+, 2019) - Huber, D.; Chaplin, W. J.; Chontos, A.; Kjeldsen, H.; Christensen-Dalsgaard, J.; Bedding, T. R.; Ball, W.; Brahm, R.; Espinoza, N.; Henning, T.; Jordan, A.; Sarkis, P.; et al. (VizieR Online Data Catalog, 2019)
We obtained high-resolution spectra of HD 221416 using several facilities within the TESS Follow-up Observation Program (TFOP), including HIRES (Vogt et al. 1994SPIE.2198..362V) on the 10 m telescope at Keck Observatory (Maunakea, Hawai'i); the Hertzsprung SONG Telescope at Teide Observatory (Tenerife; Grundahl et al. 2017ApJ...836..142G); HARPS (Mayor et al. 2003Msngr.114...20M), FEROS (Kaufer et al. 1999Msngr..95....8K), Coralie (Queloz et al. 2001Msngr.105....1Q), and FIDEOS (Vanzi et al. 2018MNRAS.477.5041V) on the MPG/ESO 3.6 m, 2.2 m, 1.2 m, and 1 m telescopes at La Silla Observatory (Chile); Veloce (Gilbert et al. 2018SPIE10702E..0YG) on the 3.9 m Anglo-Australian Telescope at Siding Spring Observatory (Australia); TRES (Furesz 2008, PhD thesis Univ. Szeged) on the 1.5 m Tillinghast reflector at the F. L. Whipple Observatory (Mt. Hopkins, Arizona); and iSHELL (Rayner et al. 2012SPIE.8446E..2CR) on the NASA IRTF Telescope (Maunakea, Hawai'i). All spectra used in this paper were obtained between 2018 November 11 and December 30 and have a minimum spectral resolution of R~44000. (1 data file).
Keywords: Exoplanets; Radial velocities; Stars: bright; Stars: late-type